Hemangiomas and Vascular Malformations: Current Theory and Management - Gresham T. Richter; Adva B. Friedman (International Journal of Pediatrics)
Vascular anomalies are a heterogeneous group of congenital blood vessel disorders more typically referred to as birthmarks. Subcategorized into vascular tumors and malformations, each anomaly is characterized by specific morphology, pathophysiology, clinical behavior, and management approach. Hemangiomas are the most common vascular tumor. Lymphatic, capillary, venous, and arteriovenous malformations make up the majority of vascular malformations. This paper reviews current theory and practice in the etiology, diagnosis, and treatment of these more common vascular anomalies.